TNF-alpha and IL-17 cytokine levels in Brazilian patients with ankylosing spondylitis after anti-TNF therapy (Brazilian Journal of Pharmaceutical Sciences, 2023)
The aim of this study was to evaluate tumor necrosis factor alpha (TNF-α), interleukin (IL)- 17A/F levels in the serum of ankylosing spondylitis (AS) patients after anti-TNF therapy, in order to understand how these cytokines are involved in this therapeutic response. Forty-four AS patients were included in the study: thirty using anti-TNF therapy were classified according to their therapy response as responders (15) and non-responders (15) and 14 without anti-TNF therapy were classified as AS control. Fifteen healthy individuals formed the control group. Serum levels of TNF-α were determined using Luminex technology and for IL-17A and IL-17F using ELISA. The non-responder patients presented higher serum levels of TNF-α than the responders and AS control; the same results were found when HLA-B*27 positive or negative patients were separately analyzed. IL-17A and IL17F serum levels were similar for all groups. According to the clinical disease activity, AS patients with BASDAI ≥4 had higher serum levels of TNF-α than AS patients with BASDAI <4. Positive correlation was found between TNF-α levels and BASDAI. In AS patients, TNF-α serum levels were associated with anti-TNF therapy and disease activity independently of HLA-B*27, and IL-17A and IL-17F were not related to anti-TNF treatment.